The study of supportive activities during pregnancy on postpartum depression - Ajh N; Unesian; Fili A; Abasi Motejaded (Tehran University of Medical Sciences, 2006)
Background & Aim: Postpartum depression is mood disorder that affected 10-15% of women during 6 months after delivery. This study was designed to investigate preventive effect of supportive activities during prenatal on postpartum depression. Methods & Materials: This research is clinical trial study and the samples were 440 pregnant women in Lahijan and Astanea in eastern of Gilan .The sampling was simple randomization for 2 groups. One group presented in education classes and others received current prenatal care. Between 4 to 8 weeks after delivery their Beck depression inventory (BDI) score was evaluated among two groups. Data analysis has been done by SPSS statistical software. Results: Prevalence depression (cases who have Beck score more than 16) in study group was 6.5% versus 18.6% in control group. Mean BDI score in study group was 7.08 versus 8.69. Conclusion: Participated to education classes during pregnancy decrease the postpartum depression.